2012
DOI: 10.4103/0253-7613.93853
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic and antihyperlipidemic effects of ethanolic extract of leaves of Punica granatum in alloxan-induced non-insulin-dependent diabetes mellitus albino rats

Abstract: Objectives:Punica granatum L., (Family: Punicaceae) is used in Indian Unani medicine for treatment of diabetes mellitus. Therefore, the present study was done to evaluate the antidiabetic and antihyperlipidemic effects of ethanolic extract of leaves of P. granatum in alloxan-induced diabetic rats.Materials and Methods:Healthy Wistar albino rats (100-150 g) were divided into four groups of six animals each. Groups A and B received normal saline [(10 ml/kg/day/per oral (p.o.)]; group C received ethanolic extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(25 citation statements)
references
References 13 publications
1
24
0
Order By: Relevance
“…Thus, in the present study, STZ was used for induction of diabetes in rats. Administration of STZ led to significant increase in blood glucose level which was lowered on treatment with MPGL thus confirming the antihyperglycemic activity of the extract as reported by earlier established studies 13, 24. However, up to 4 weeks no significant difference was observed in the glucose level of MPGL treated groups as compared to diabetic group.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Thus, in the present study, STZ was used for induction of diabetes in rats. Administration of STZ led to significant increase in blood glucose level which was lowered on treatment with MPGL thus confirming the antihyperglycemic activity of the extract as reported by earlier established studies 13, 24. However, up to 4 weeks no significant difference was observed in the glucose level of MPGL treated groups as compared to diabetic group.…”
Section: Discussionsupporting
confidence: 86%
“…The animals were divided into 5 groups: Normal control group (n = 6), STZ-induced diabetic group (n = 6), STZ-induced diabetic group treated with MPGL 100 mg/kg (n = 6), STZ-induced diabetic group treated with MPGL 200 mg/kg (n = 6) and STZ-induced diabetic group treated with MPGL 400 mg/kg (n = 6). The three doses of extract were selected on the basis of the acute oral toxicity study reported on the plant in addition to the previous studies carried out on the plant 13, 18. Blood glucose levels were measured before treatment and on 1st, 2nd, 4th, 6th & 8th weeks respectively.…”
Section: Methodsmentioning
confidence: 99%
“…It belongs to the order of Myrtales and family of Lythraceace. More than 500 cultivators throughout the world cultivate P. granatum [8]. It is abundantly available in Himalayan regions and Kashmir.…”
Section: Introductionmentioning
confidence: 99%
“…Beside oral antiseptic, it is also used to treat periodontitis and dental carries [9]. P. granatum has anti-diabetic activity [8]. P. granatum is also used in treatment of skin infections and injuries, where its role may be attributed to its antioxidant effect [9, 10, 12].…”
Section: Introductionmentioning
confidence: 99%
“…The fruit of pomegranate is used to treat microbial infection, diarrhoea and haemorrhage (Fuentes and Exposito et al, 1995). It is used as an antiseptic and for skin infections and injuries (Kotamballi et al, 2003;Juernka, 2008; Das and Barman, 2012;Khan et al, 2013Khan et al, , 2014. Fresh leaves extract is used for dysentery, skin disease, checking of blood flow from nose and as eyewash.…”
Section: Discussionmentioning
confidence: 99%